Gut Microbiome Dysbiosis During Metabolic Disorders: Diabetes - Saksham Gupta; Sumiran Srivastava (Emerging Trends in Metabolites, 2024)
Understanding the intricate interplay between gut microbiome dysbiosis and diabetes is crucial due to the escalating prevalence and impact of diabetes mellitus globally. This comprehensive review examines the current understanding of this relationship, elucidating how alterations in the gut microbiome composition contribute to diabetes pathogenesis by influencing metabolic homeostasis, immune regulation, and insulin resistance. Dysregulation of gut microbial communities leads to shifts in diversity and abundance, exacerbating chronic low-grade inflammation and gut barrier dysfunction, which further perpetuates metabolic dysfunction. Microbial metabolites, such as short-chain fatty acids and bile acids, play pivotal roles in modulating host metabolism and immune responses, thereby influencing the development and progression of diabetes. Importantly, dietary factors significantly shape the diabetic gut microbiome, offering avenues for dietary interventions to modulate microbial composition and function. Various therapeutic strategies targeting the gut microbiome, including probiotics, prebiotics, and dietary supplements, hold promise for improving metabolic outcomes in diabetes. However, integrating these interventions into clinical practice poses challenges but offers potential benefits for optimizing treatment outcomes and reducing disease complications. Continued research efforts are essential to unravel the complex interactions between the gut microbiome and diabetes, paving the way for innovative therapeutic approaches and personalized interventions in the future. This review underscores the significance of understanding the gut microbiome-diabetes nexus and its implications for disease management and future research directions.
Keywords: Diabetes; Microbial metabolites; dysbiosis; guts microbiome; therapeutic strategies